Increasing Knowledge of the Community of Karang Rejo Village Through Actualization of Transformation to Prevent Covid-19 Characteristics of Local Excellence - Manalu, Sarah Patumona; Serepina, Zettaya (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Increasing knowledge of the community of Karang Rejo village through actualization of transformation to prevent Covid-19 characteristics of local excellence is a form of implementation of students placed in Karang Rejo Village through KKN implementation to increase public understanding in order to prevent the spread of Covid-19 based on the village's wisdom. Kuliah Kerja Nyata (KKN) in this case is a manifestation of Higher Education in upholding social values to the community by doing community service through KKN work programs. The actualization of the transformation is carried out through the implementation of work programs carried out by two methods, namely online and offline. Through the work programs that have been implemented, the public's understanding of Covid-19 and the importance of posyandu activities for pregnant women and toddlers has increased marked by changes in society that are more concerned with Covid-19 and posyandu activities.